Analgesia and Sedation Strategies in Mechanically Ventilated Adults with COVID‐19. Issue 12 (20th November 2020) - Adams, Christopher D.; Altshuler, Jerry; Barlow, Brooke L.; Dixit, Deepali; Droege, Christopher A.; Effendi, Muhammad K.; Heavner, Mojdeh S.; Johnston, Jackie P.; Kiskaddon, Amy L.; Lemieux, Diana G.; Lemieux, Steven M.; Littlefield, Audrey J.; et al.
Abstract : Evidence‐based management of analgesia and sedation in COVID‐19‐associated acute respiratory distress syndrome remains limited. Non‐guideline recommended analgesic and sedative medication regimens and deeper sedation targets have been employed for patients with COVID‐19 due to exaggerated analgesia and sedation requirements with extended durations of mechanical ventilation. This, coupled with a desire to minimize nurse entry into COVID‐19 patient rooms, marked obesity, altered end‐organ function, and evolving medication shortages, presents numerous short‐ and long‐term challenges. Alternative analgesic and sedative agents and regimens may pose safety risks and require judicious bedside management for appropriate use. The purpose of this commentary is to provide considerations and solutions for designing safe and effective analgesia and sedation strategies for adult patients with considerable ventilator dyssynchrony and sedation requirements, such as COVID‐19.